PENYELESAIAN SENGKETA EKONOMI SYARIAH DI INDONESIA JALUR LITIGASI DAN NON-LITIGASI - Mauli Mustika Nur Safitri (Program Studi Ekonomi Syariah, 2025)
The rapid development of Islamic economic activities in Indonesia has given rise to a wider range of potential disputes, both due to differences in the interpretation of contracts and inconsistencies in the application of Islamic principles. This study stems from concerns about the uncertainty of dispute resolution forums, especially after changes in national regulations and the dynamics of DSN-MUI fatwas. Using a qualitative research method based on a literature review, this study examines laws, PERMA, DSN-MUI fatwas, and related academic literature. The results show that dispute resolution through litigation has been significantly strengthened after the enactment of Law No. 3/2006, Law No. 21/2008, and PERMA No. 14/2016, making the Religious Court the official institution authorized to handle sharia economic cases. On the other hand, non-litigation mechanisms, including deliberation, negotiation, mediation, conciliation, and arbitration through BASYARNAS, remain an important option due to their faster, more flexible nature and minimal potential for further conflict. An analysis of the DSN-MUI fatwa shows a development in the direction of dispute resolution, from initially emphasizing deliberation and arbitration to later opening up the possibility of litigation in the Religious Court. This finding highlights the importance of synchronization between state regulations, dispute resolution mechanisms, and fatwa provisions so that the resolution process can proceed in accordance with the principles of sharia justice.